Effect of Compost and Hydroabsorbent Polymer on Tree Growth and Soil Properties in a Tropical Urban Environment. Issue 10 (31st May 2018) - Ghosh, Subhadip; Pal, Pranoy; Ow, Lai Fern; Burcham, Daniel C.; Rakshit, Amitava
ABSTRACT: Horticultural application of hydroabsorbent polymer (HP) has drawn research attention due to its perceived benefits to plant growth. Few studies have compared the use of compost and HP amendments on tree establishment in tropical urban environments. An experiment was conducted to assess the effect of compost (40% v v –1 ) and HP (3 and 5 kg m –3 ) on the growth of two native tree saplings ( Calophyllum soulattri and Syzygium myrtifolium ) in loamy and sandy soils. The HP treatments significantly affected soil pH and extractable phosphorus (P) and potassium (K), whereas combined application of compost and HP (5 kg m –3 ) resulted in significantly higher nitrogen (N) in both soil types. Plant diameter and height were significantly higher following HP application. This experiment demonstrates the efficacy of HP that can cater the plant requirements at the initial growth stages which are crucial for their successful establishment in tropic urban degraded soils.